PRESENTATION OF POLYCYSTIC OVARY SYNDROME AND ITS MANAGEMENT WITH CLOMIPHENE ALONE AND IN COMBINATION WITH METFORMIN - Raja, Ayisha; Hashmi, Shoaib Naiyar; Sultana, Nadra; Rashid, Haroon (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried out to determine the pattern of presentation of Polycysitc ovary syndrome (PCOS) in patients presenting at our unit and to compare effects of clomiphene alone and in combination with metformin in management of PCOS. Methods: This study was conducted was conducted from Jan 2001-2003 at Military Hospital, Rawalpindi. All patients presenting with infertility were evaluated with a view to select 100 patients of PCOS with the help of history of oligomenorrhoea, hirsuitism and acne. Diagnosis was confirmed by ultrasonography and hormone analysis (LH, FSH, prolactin, testosterone along with LH:FSH>2). The 100 selected patients were divided into two equal groups, one was given combined clomiphene citrate (CC) and metformin for ovulation induction and the other CC alone. These patients were followed for six cycles for ovulation and conception. Follicle tracking on ultrasonography and day-21 serum progesterone level were used to detect ovulation while conception was confirmed by urine pregnancy test, serum B - HCG level and ultrasonography for gestational sac. Results: Hirsuitism and oligomenorrhoea were the two most common clinical features of PCOS. In the first group 34 patients (68%) ovulated as compared with 18 (36%) in the second group. In the first group 18 out of 34 women (52.9 %) conceived as compared with only 8 out of 18 (44%) in the second group. The difference was significant at >0.05 when ovulatory and pregnancy responses were compared among two groups. All patients tolerated metformin well and no teratogenic effects were observed in patients who conceived after treatment with metformin. Conclusion: A combination of metformin and clomiphene citrate significantly increases the ovulation and conception rates in these patients. KEY WORDS: PCOS, metformin, ovulation induction.